Concern with dental appearance and associated factors among the elderly of two southern Brazilian cities - Diandra Genoveva Sachetti; Fernanda Pretto Zatt; Thais Carleso Trevizan; Caroline Fernandes e Silva; Francisco Wilker Mustafa Gomes Muniz; Cassiano Kuchenbecker Rösing; Paulo Roberto Grafitti Colussi (Universidade Estadual de Campinas, 2020)
Aim: This study aimed to evaluate the prevalence of concern with dental appearance (DA) and associated factors among the elderly of two southern Brazilian cities. Methods: A cross-sectional study was conducted in the cities of Cruz Alta and Veranópolis, Brazil. Oral health examination and a structured questionnaire were applied. Questions from the PCATool-SB Brasil tool and the Questionnaire about Teeth Appearance, both validated to Brazilian samples, were used. The collected independent variables were: sex, age, ethnicity, education level, marital status, retirement, health problem, use of medication, smoking exposure, alcohol exposure, access to the dentist, toothbrushing frequency, use of dental floss, edentulism, use of and need for dental prosthesis. Concern with DA was dichotomized into yes/no. Associations between dependent and independent variables were assessed by Chi-square or Mann-Whitney tests. Moreover, uni- and multivariate analyses were conducted by Poisson regression with robust variance. Level of significance was established as p<0.05. Results: The prevalence of concern with DA was 18.8% (n=107). The prevalence ratio (PR) of concern with DA decreased 5.8% for each year increase (PR:0.942; 95% confidence interval [95%CI]:0.911-0.973). Elderly without access to the dentist in the last 12 months presented 62.5% (p=0.006) higher PR of concern with DA when compared to those with access to dental care. Dentate elderly showed 219% higher PR for concern with DA (PR:2.197; 95%CI:1.364-3.539) in comparison to edentulous individuals. Conclusion: Prevalence of concern with DA was low and associated with demographics, access to dental care and edentulism.